A SCOPING REVIEW OF PARENTAL DETERMINANTS OF STUNTING IN CHILDREN UNDER FIVE IN LOW AND MIDDLE INCOME COUNTRIES - Jusrawati Jusrawati; Endang Koni Suryaningsih (Journal of Nutrition College, 2026)
ABSTRACTBackground: Stunting in children under five is a critical global health issue, particularly in Low and Middle-Income Countries (LMICs). The aetiology is complex, and parental characteristics are recognised as key determinants. However, a comprehensive synthesis of this evidence is limited.Objective: This scoping review aims to synthesise and map the available scientific evidence on the parental determinants of stunting in children under five in LMICs.Method: The review followed the Arksey and O’Malley framework. A systematic search was conducted across four databases for English-language research articles published between 2015 and 2025. After screening, 19 articles (1 qualitative, 18 quantitative) were included for analysis.Results: The literature synthesis identified three main categories of parental determinants: socio-demographic factors (education, socioeconomic status), biological and psychosocial factors (maternal nutritional status, mental health), and caregiving practices (exclusive breastfeeding, complementary feeding). The majority of studies were cross-sectional, establishing a strong association between these factors and stunting.Conclusion: Stunting is profoundly influenced by the complex interaction of various parental characteristics. These findings highlight the need for a holistic approach to stunting prevention that goes beyond child nutrition to focus on parental empowerment. Policy interventions should prioritise improving nutritional literacy, providing socioeconomic support, and enhancing maternal mental health care.Keywords: Stunting; parental determinants; children under five; scoping review; LMICs